2014
DOI: 10.1080/00222895.2014.924473
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilesional Arm Motor Sequence Performance After Right and Left Hemisphere Damage

Abstract: Aiming movements are part of daily activities but the brain hemispheres' role in targeted aiming sequential movements is not fully clear. Start and execution of discrete and sequential tasks toward targets were analyzed in 10 individuals with left-hemisphere damage, 10 right-hemisphere-damaged, and 10 healthy ones. Arm movements were performed over a digitizing tablet, following stimuli on a monitor, from initial position toward right and left-positioned targets. Poststroke individuals used their ipsilesional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Previous work suggests that deficits in the ipsilesional arm and hand varies with the severity of contralesional deficits, especially in the sub-acute and chronic phase after stroke (5)(6)(7)(8). More interestingly, the unilateral motor deficits observed for contralesional and ipsilesional limbs seem to be hemisphere-specific and thus depend on side of stroke lesion (9)(10)(11)(12)(13)(14)(15). For predominantly righthanded cohorts, contralesional deficits appear to be more severe in those with right hemisphere damage (RHD), in whom the contralesional limb is non-dominant.…”
Section: Introductionmentioning
confidence: 93%
“…Previous work suggests that deficits in the ipsilesional arm and hand varies with the severity of contralesional deficits, especially in the sub-acute and chronic phase after stroke (5)(6)(7)(8). More interestingly, the unilateral motor deficits observed for contralesional and ipsilesional limbs seem to be hemisphere-specific and thus depend on side of stroke lesion (9)(10)(11)(12)(13)(14)(15). For predominantly righthanded cohorts, contralesional deficits appear to be more severe in those with right hemisphere damage (RHD), in whom the contralesional limb is non-dominant.…”
Section: Introductionmentioning
confidence: 93%
“…Finally, we identify the limitations of this study and suggest future research questions. movements 15 , and thus, injury to the left hemisphere, particularly to premotor and fronto-parietal networks (e.g. IPC) 27, 28 may impair planning and sequencing required for smooth and rapid performance of dexterous motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition to the studies aimed at characterizing the relationship between contralesional and ipsilesional hands, there is mounting evidence that the unilateral motor deficits observed for contralesional and ipsilesional are hemisphere-specific and thus depend on side of stroke lesion. 8, [11][12][13][14][15][16] For example, using clinical motor assessments of grip strength and hand dexterity, Harris and Eng 13 showed that in chronic stroke survivors who are pre-morbidly right-hand dominant, contralesional motor impairments were less severe in individuals who suffered damage in the dominant (i.e. left) hemisphere (LHD) compared to those who suffered damage in the non-dominant (right) hemisphere (RHD).…”
Section: Introductionmentioning
confidence: 99%
“…A vest was used to restrict trunk-associated movements (Figure 1). Silva et al, 2014. Prior to starting the experimental task, participants were familiarized with the experimental apparatus by moving the cursor toward targets located on the monitor screen in different positions from those analyzed during the experiment to avoid learning effects. Subsequently, the calibration of the targets position was made.…”
Section: Methodsmentioning
confidence: 99%
“…The direction of the movement also influences its execution. In most movement directions, the intersegmental coordination of the limb creates an interaction torque in the elbow joint due to the active movement of the shoulder (Dounskaia, 2005(Dounskaia, , 2010Dounskaia, Goble, & Wang, 2011;Dounskaia, Ketcham, & Stelmach, 2002).This coordination can be seen mostly in contralateral movements, which are slower, less smooth, and less precise than those directed to ipsilateral targets (Coqueiro, de Freitas, Silva, & Alouche, 2014;Ishihara et al, 2002;Silva, de Freitas, Silva, Banjai, & Alouche, 2014). For ipsilateral movements, fundamentally in the diagonal direction on the same side as the upper limb performing the movement, the elbow joint is responsible for starting the movement by active torque (Dounskaia, 2005(Dounskaia, , 2010Dounskaia et al, 2002;Galloway & Koshland, 2002).…”
Section: Introductionmentioning
confidence: 99%